Radiation enhancement of laser palliation for malignant dysphagia: a pilot study. Issue 12 (December 1992) - Sargeant, I R; Loizou, L A; Tobias, J S; Blackman, G; Thorpe, S; Bown, S G
Abstract : Laser therapy offers rapid relief of dysphagia for patients with cancers of the oesophagus and gastric cardia but repeat treatments are required approximately every five weeks to maintain good swallowing. To try to prolong the treatment interval, 22 elderly patients were given additional external beam radiotherapy. Nine had squamous cell carcinoma and 13 adenocarcinoma: five had documented metastases. Six received 40 Gy and 16, 30 Gy in 10-20 fractions. A 'check' endoscopy was performed three weeks after external beam radiotherapy. Dysphagia was graded from 0-4 (0 = normal; 4 = dysphagia for liquids). The median dysphagia grade improved from 3 to 1 after laser treatment. This improvement was maintained in the 30 Gy group but there was a noticeable deterioration in three of those who had received the higher radiation dose. A lifelong dysphagia grade of 2 or better was enjoyed by 14 of 16 patients in the 30 Gy group but only two of six in the 40 Gy group. The dysphagia controlled interval was 9 weeks (median) after check endoscopy and subsequent endoscopic procedures were required every 13 weeks to maintain good swallowing. There were no endoscopy related complications. Combined treatment is a promising approach for reducing the frequency of endoscopic treatments. The 30 Gy dose seems more appropriate and may prolong survival. A randomised study to test these conclusions is in progress.